A thematic exploration of social media analytics in marketing research and an agenda for future inquiry. (18th August 2021) - Wang, Yun; Deng, Qi; Rod, Michel; Ji, Shaobo
ABSTRACT: This paper aims to present the current social media analytics in marketing research. A bottom-up thematic content analysis of 123 academic papers from 38 top Marketing and Information Systems journals was conducted. Types of social media platform, data, and analytics; marketing themes; and fields of study that are involved in social media analytics research are identified. The match between technological inputs and marketing outputs is presented. The findings reveal the current status of social media analytics in marketing research and identify various untapped areas for further research. This paper proposes that the impact of social media analytics is not restricted as a marketing research method; it fosters or amplifies changes in marketing approach, and structure and culture in organisations. To maximise its benefits, this paper suggests that firms could strategically build a technological knowledge base of social media analytics, and strategically manage and support its use by facilitating IT-marketing and IT-organisation alignments.